2020
DOI: 10.1182/blood.2019000931
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Castleman disease

Abstract: Castleman disease (CD) describes a group of at least 4 disorders that share a spectrum of characteristic histopathological features but have a wide range of etiologies, presentations, treatments, and outcomes. CD includes unicentric CD (UCD) and multicentric CD (MCD), the latter of which is divided into idiopathic MCD (iMCD), human herpes virus-8 (HHV8)-associated MCD (HHV8-MCD), and polyneuropathy, organomegaly, endocrinopathy, monoclonal plasma cell disorder, skin changes (POEMS)-associated MCD (POEMS-MCD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
453
2
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 293 publications
(476 citation statements)
references
References 94 publications
5
453
2
16
Order By: Relevance
“…Overall, the course of the disease does not strictly follow that of the underlying neoplasm, nonetheless there is a general consensus that early treatment of the neoplasm, especially in the presence of Castleman's disease or thymoma, followed by rapid immunosuppressive treatment, will dampen PNP symptoms [155,156]. Based on the evidence of increased levels of IL-6 in PNP sera and the crucial role of IL-6 in Castleman's disease [157,158], tocilizumab, a monoclonal antibody targeting IL-6, has been successfully applied as a treatment for PNP in this context, but seems to have limited effect in preventing bronchiolitis obliterans [159,160]. Rituximab, with or without chemotherapy, represents an effective therapeutic option for PNP [146,161]; thymoma-associated PNP or multi-organ syndrome also respond well to rituximab treatment, but a significant proportion of these patients still die as a result of infections and sepsis [137].…”
Section: Paraneoplastic Pemphigusmentioning
confidence: 99%
“…Overall, the course of the disease does not strictly follow that of the underlying neoplasm, nonetheless there is a general consensus that early treatment of the neoplasm, especially in the presence of Castleman's disease or thymoma, followed by rapid immunosuppressive treatment, will dampen PNP symptoms [155,156]. Based on the evidence of increased levels of IL-6 in PNP sera and the crucial role of IL-6 in Castleman's disease [157,158], tocilizumab, a monoclonal antibody targeting IL-6, has been successfully applied as a treatment for PNP in this context, but seems to have limited effect in preventing bronchiolitis obliterans [159,160]. Rituximab, with or without chemotherapy, represents an effective therapeutic option for PNP [146,161]; thymoma-associated PNP or multi-organ syndrome also respond well to rituximab treatment, but a significant proportion of these patients still die as a result of infections and sepsis [137].…”
Section: Paraneoplastic Pemphigusmentioning
confidence: 99%
“…A recent study using NGS of unicentric Castleman's diseases lymph node tissue revealed somatic platelet‐derived growth factor receptor β (PDGFRb) mutations in nearly 20% of cases 96 . Uncontrolled HHV8 infection is likely the etiological driver in multi‐centric Castleman's diseases 97 . In immunocompromised individuals, HHV8 can replicate in lymph node plasmablasts leading to synthesis and release of several cytokines among which IL‐6 that is able to activate STAT3 and NF‐kB pathways 97 …”
Section: Non‐hodgkin Lymphoma‐related Peripheral Neuropathiesmentioning
confidence: 99%
“…Uncontrolled HHV8 infection is likely the etiological driver in multi‐centric Castleman's diseases 97 . In immunocompromised individuals, HHV8 can replicate in lymph node plasmablasts leading to synthesis and release of several cytokines among which IL‐6 that is able to activate STAT3 and NF‐kB pathways 97 …”
Section: Non‐hodgkin Lymphoma‐related Peripheral Neuropathiesmentioning
confidence: 99%
“…Castleman disease (CD), or angiofollicular hyperplasia or giant lymph node hyperplasia, is a rare non-neoplastic lymphoproliferative disorder with variable clinicopathologic subtypes. 1,2 It was first described by Castleman et al in 1954 in a group of patients with localized lymph node hyperplasia. 2,3 The etiology of CD remains largely unknown; the pathogenesis show inflammatory response to a mysterious antigenic stimulus with chemical mediators (cytokines) of inflammation particularly interleukin-6 (IL6) playing a prominent role.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It was first described by Castleman et al in 1954 in a group of patients with localized lymph node hyperplasia. 2,3 The etiology of CD remains largely unknown; the pathogenesis show inflammatory response to a mysterious antigenic stimulus with chemical mediators (cytokines) of inflammation particularly interleukin-6 (IL6) playing a prominent role. 1,2 CD can be categorized histomorphologically into three distinct subtypes, namely: hyaline vascular, plasma cell, and mixed hyaline vascular plasma cell types.…”
Section: Introductionmentioning
confidence: 99%